If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7g + -15 = g + -3 Reorder the terms: -15 + 7g = g + -3 Reorder the terms: -15 + 7g = -3 + g Solving -15 + 7g = -3 + g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1g' to each side of the equation. -15 + 7g + -1g = -3 + g + -1g Combine like terms: 7g + -1g = 6g -15 + 6g = -3 + g + -1g Combine like terms: g + -1g = 0 -15 + 6g = -3 + 0 -15 + 6g = -3 Add '15' to each side of the equation. -15 + 15 + 6g = -3 + 15 Combine like terms: -15 + 15 = 0 0 + 6g = -3 + 15 6g = -3 + 15 Combine like terms: -3 + 15 = 12 6g = 12 Divide each side by '6'. g = 2 Simplifying g = 2
| 2x+x^2+144=0 | | 85-3x=2x+10 | | (4-2k+3l)+(2-3k-2l)= | | 135-2x=34x+15 | | -104-7x=10x+15 | | 2x+12=-38-8x | | y=-32x^2-6x | | y=-32x^2-6x | | y=-32x^2-6x | | 2x^2+30=0 | | 14-10x=74-24x | | -37-7x=7x+20 | | (7z-3)-(4z-11)=47 | | 6t-5=2t-5 | | 266-6x=39x+21 | | 3r+6=18 | | 7x(-2x+3)=0 | | 6x(4x+3)=0 | | 2(2)-3y=-9 | | -50+x=-10 | | 40x-6=9 | | -4(x+3)=x+8 | | 6x(4x-1)=0 | | 5x-10x=x-12 | | 172-6x=6x+16 | | -(-2x)=(-88) | | 2(x+4)=5x-1 | | 6p+12=4p | | -4x+12=x+17 | | 12-9x=52-16x | | 3x-7=-4x | | 3x-7=-1 |